Knowledge and Attitude Towards Cervical Cancer and its Screening among Women Attending the Gynecology Out Patient Department : Cervical Cancer and its Screening - Siddiqa, Ayesha; Iqbal, Saba; Hameed, Wajiha; Saba, Ambreen; Khalid, Uzma; Younas, Naila; Bashir, Fouzia; Aslam, Hina; Karam Din, Saima (Pakistan Journal of Health Sciences, 2023)
A kind of cervix cancer called cervical cancer arises when the cells in the cervix divide too rapidly. The costs of cervical cancer are considerable for the woman, her family, and society as a whole. Women’s attitudes and understanding on cervical cancer screening are the subject of this study. Objective: To determine the Knowledge and attitude towards cervical cancer and its screening among women attending the Gynecology Out Patient Department and to evaluate the factors associated with knowledge and attitude towards cervical cancer and its screening. Methods: This study was carried out using a cross-sectional design. 15 women visiting the Gynaecology OPD were recruited through convenient sampling technique. A structured questionnaire encompassing socio-demographic characteristics, knowledge, and attitudes was utilized to collect data, which was then analyzed using SPSS version-24. Results: According to the study’s findings, 65 (43%) of the 122 participants were between the ages of 31 and 40, and 94 (74.7%) were housewives. About 106 (70.7%) of respondents had low understanding of cervical cancer screening, whereas 44 (29.3%) had strong knowledge. The results suggest that respondents’ knowledge of cervical cancer screening was significantly related to their education, marital status, occupation, and place of residence. The respondents’ attitudes regarding cervical cancer screening were also significantly related to their education, occupation, and place of residence. Conclusions: The study revealed that women visiting the Gynaecology department have insufficient knowledge and attitudes about cervical cancer and screening. There is a need to enhance women’s understanding and attitudes towards cervical cancer screening in order to detect and treat the illness early.